Prediction of Green Purchase Intention for Electric Vehicles: A Theory of Planned Behavior Approach - Solekah, Nihayatu Aslamatis; Ratnasari, Kartika; Hirmawan, Ari Prasetyo (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
The campaign to switch to electric vehicles (EVs) has been reinforced to reduce global air pollution and greenhouse gas emissions. This study focuses on expanding the theory of planned behavior by adding external factors (charging facilities and vehicle performance) and individual factors (environmental concerns and knowledge), leading to green purchase behavior for electric vehicles. Data were collected from 239 respondents who use electric vehicles in East Java, Indonesia, and analyzed using Smart PLS. The results showed that Attitude, Subjective Norm, Knowledge, and Vehicle Performance affected Green purchase intention for Electric Vehicles (GPIEV). However, environmental concerns and Perceived behavioral control and Charging Facilities did not affect GPIEV. The results imply that attitudes in the form of perceptions about particular behaviors directly contribute to their interest in purchasing electric vehicles.